2022
DOI: 10.3389/fpubh.2022.974419
|View full text |Cite
|
Sign up to set email alerts
|

Association between early childhood caries and diet quality among Chinese children aged 2–5 years

Abstract: BackgroundEarly childhood caries (ECC) is a major oral problem affecting the health and wellbeing of children worldwide. Diet quality is a better predictor of ECC risk than single foods or specific nutrients. The purposes of this study were to assess the associations between ECC and diet quality among 2- to 5-year-old Chinese children.MethodsA total of 150 eligible children were included in this study. The decayed, missing, or filled surface (dmfs) score was recorded for each child by dental examination. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Infant dietary practices, particularly the consumption of sugary beverages, have been linked to the occurrence of ECC among preschoolers [ 26 ]. Notably, a study involving Chinese children aged two to five years revealed that heightened food diversity correlated with reduced caries prevalence [ 27 ]. Additionally, frequent consumption of simple carbohydrates, primarily dietary sugars, significantly escalates the risk of dental caries [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…Infant dietary practices, particularly the consumption of sugary beverages, have been linked to the occurrence of ECC among preschoolers [ 26 ]. Notably, a study involving Chinese children aged two to five years revealed that heightened food diversity correlated with reduced caries prevalence [ 27 ]. Additionally, frequent consumption of simple carbohydrates, primarily dietary sugars, significantly escalates the risk of dental caries [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…Caries is a sugar-dependent disease that causes demineralization of enamel, which is caused by the increasing acidity of the microenvironment produced by a selective group of bacteria [1] . The American Academy of Pediatric Dentistry defines early childhood caries (ECC) when a child under 71 months of age has one or more decayed (with or without cavitation lesions), absent (due to caries) or filled (dmfs) tooth surfaces on any primary tooth [2] . In developed countries, its prevalence is between 1% and 12%, but can reach 70% in high-risk populations, such as low socioeconomic groups or ethnic minorities [3] .…”
Section: Introductionmentioning
confidence: 99%